Rescue jack system applying hydrogen-absorbing alloys as a pressure source. (6th December 2018) - Hosono, Minako; Sakaki, Kouji; Nakamura, Yumiko; Ino, Shuichi
Abstract: This paper presents a flexible and compact rescue jack system that uses a hydrogen-absorbing alloy as its pressure source. The jack system comprises a container for the hydrogen-absorbing alloy and an end effector thin enough to be applied within a 2 mm-thick gap, made of a fiber-reinforced rubber bag. The hydrogen-absorbing alloy (LaNi4.45 Co0.5 Mn0.05 ), whose plateau pressure was set to near atmospheric pressure at 25 °C, released hydrogen gas when heated to 50 °C. Experiments showed the system could lift 100 kg at moderate speed when the alloy container was placed in hot water (50 °C). Moreover, the jack system could maintain a 50 mm lift of 100 kg for nearly 12 h—performance comparable with that of an air jack. This clearly indicates the fiber-reinforced rubber bag is a suitable end effector of the actuator. The proposed jack system has good potential for prompt rescue activities conducted by non-professional operatives. Highlights: Rescue jack system using hydrogen-absorbing alloy as its pressure source is proposed. Thin and flexible end effector is capable of deployment in 2-mm-thick gaps. Rescue jack system can lift 100 kg by 50 mm when alloy is placed in 50 °C water. Rescue jack system can sustain a lift of 100 kg by 50 mm for nearly 12 h.